Fall Risk and Balance Confidence in Patients With Diabetic Peripheral Neuropathy: An Observational Study - Riandini, Tessa; Khoo, Eric Y. H.; Tai, Bee Choo; Tavintharan, Subramaniam; Phua, Melissa S. L. A.; Chandran, Kurumbian; Hwang, Siew Wai; Venkataraman, Kavita (Frontiers in Endocrinology, 2020)
Objective: Individuals with diabetic peripheral neuropathy (DPN) have functional deficits that increase their risk of falling. However, psychological aspects such as loss of confidence in undertaking activities could also contribute to this risk. We examined correlations between balance confidence and fall risk among individuals with DPN. Methods: This was a cross-sectional study of 146 individuals with DPN. Elevated fall risk was determined by timed up-and-go test with standard cut-off time of 13.5 seconds, and balance confidence was measured by 16-item Activities Based Balance Confidence scale. Functional parameters assessed included functional reach, body sway velocity during quiet standing and muscle strength at ankle and toe. Results: Twenty percent of the DPN patients were at increased risk of falls. Every unit increase in balance confidence was associated with 9% (95% confidence interval: 0.88, 0.95; p<0.001) reduced odds of falling, after adjusting for socio-demographic, health and functional characteristics. No other functional parameters had significant associations with fall risk in adjusted analyses. Conclusions: Psychological factors like balance confidence appear to be more important for fall risk among DPN patients, compared to objective functional performance. Interventions targeting balance confidence may be beneficial in reducing the risk of falls in this population.